PENERAPAN STRATEGI TRIKSA (TIGA RUANG INTERAKSI SISWA) DALAM KEGIATAN DISKUSI DAN PRESENTASI TEKS DESKRIPTIF: STUDI DESKRIPTIF KUALITATIF - Annisa Cahya Rahina; Pertiwi Nurfebrianti (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to describe the implementation of the TRIKSA strategy (Tiga Ruang Interaksi Siswa) in descriptive text discussion and presentation activities to develop seventh-grade students’ speaking skills. The TRIKSA strategy is designed to provide gradual interaction spaces through individual, group, and pair activities to encourage students to express ideas and opinions more actively. This research employed a qualitative descriptive approach. The research subjects consisted of seventh-grade students and an Indonesian language teacher. Data were collected through observation, interviews, and documentation. The data were analyzed using an interactive analysis model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The results showed that the implementation of the TRIKSA strategy through three interaction spaces—individual, group, and pair—encouraged students to be more active in descriptive text discussion and presentation activities. Students demonstrated increased confidence in speaking, improved ability to organize ideas, and more balanced participation during learning activities. Students also showed positive responses to the TRIKSA strategy as learning became more interactive and varied. Several challenges were identified, including time management, differences in students’ abilities, and initial adaptation to the TRIKSA stages. These findings indicate that the TRIKSA strategy provides flexible interaction spaces that support the development of students’ speaking skills. Keywords: TRIKSA strategy, speaking skills, descriptive text